Understanding and mitigating social risks to sustainable development in China's BRI: Evidence from Nepal and Zambia - Shawn Shieh; Lowell Chow; Zhong Huang; Jinfei Yue (Overseas Development Institute (ODI), 2021)
The Belt and Road Initiative (BRI)'s focus on energy, transportation and other types of infrastructure has the potential to make an important contribution to filling the 'infrastructure gap' in BRI partner countries in the Global South. But the rapid influx of infrastructure projects and other commercial activity in those countries can also give rise to, or exacerbate, a range of social risks for local communities and workers. While Chinese state and business actors have made progress in addressing risks linked to commercial activity, the social and environmental risks to affected local communities and workers remain a significant concern. Based on a 2019 fact-finding mission to Nepal and Zambia, this report identifies the more salient social risks associated with Chinese commercial activity in those countries and provides recommendations on how Chinese and host country stakeholders can better address them. The findings are based on an extensive review of the literature on social risks associated with the BRI, and semi-structured interviews with a wide range of stakeholders in Nepal and Zambia.
Keywords: 330; Zambia; China; Nepal; Social protection